2022
DOI: 10.1186/s12934-022-01815-3
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of eriodictyol from tyrosine by Corynebacterium glutamicum

Abstract: Background Eriodictyol is a bioactive flavonoid compound that shows potential applications in medicine development and food processing. Microbial synthesis of eriodictyol has been attracting increasing attention due to several benefits. In this study, we employed a GRAS strain Corynebacterium glutamicum as the host to produce eriodictyol directly from tyrosine. Results We firstly optimized the biosynthetic module of naringenin, the upstream interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…HpaBC is widely used for the hydroxylation of some aromatic compounds. HpaB utilizes FADH 2 , which is reduced by HpaC, adding a hydroxyl group to the structure of the substrate to give FAD, and continues to be used in the next cycle. HpaBC has often been selected to catalyze the hydroxylation step in the biosynthesis of hydroxytyrosol. ,, Therefore, HpaBC from E.…”
Section: Discussionmentioning
confidence: 99%
“…HpaBC is widely used for the hydroxylation of some aromatic compounds. HpaB utilizes FADH 2 , which is reduced by HpaC, adding a hydroxyl group to the structure of the substrate to give FAD, and continues to be used in the next cycle. HpaBC has often been selected to catalyze the hydroxylation step in the biosynthesis of hydroxytyrosol. ,, Therefore, HpaBC from E.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [ 144 ] reported the highest eriodictyol titer (3.3 g/L) to date by identifying and optimizing efficient Sm CPR and Sm F3′H from Silybum marianum in S. cerevisiae , demonstrating that S. cerevisiae is an attractive platform for P450 enzyme expression involved in flavonoid biosynthesis. In another study, Corynebacterium glutamicum (a GRAS strain) was used as a host for the first time to directly produce eriodictyol (14.10 mg/L) from tyrosine by introducing matC and matB genes from Rhizobium trifolii , as well as hpaBC genes expressing 4-hydroxyphenylacetate 3-hydroxylase from Escherichia coli [ 145 ].…”
Section: Metabolic Engineering Of Flavonoid Pathwaysmentioning
confidence: 99%
“…Therefore, the production of (2 S )-eriodictyol in prokaryotes is restricted, resulting in only low-level titers. To overcome this limitation, Wu et al applied the non-P450 enzyme HpaBC to catalyze the conversion between (2 S )-naringenin and (2 S )-eriodictyol in Corynebacterium glutamicum, obtaining 14.10 mg/L (2 S )-eriodictyol . Furthermore, our group previously truncated the transmembrane regions of F3′H and CPR and fused them to generate a soluble expression enzyme in E.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, Wu et al applied the non-P450 enzyme HpaBC to catalyze the conversion between (2S)-naringenin and (2S)eriodictyol in Corynebacterium glutamicum, obtaining 14.10 mg/L (2S)-eriodictyol. 14 Furthermore, our group previously truncated the transmembrane regions of F3′H and CPR and fused them to generate a soluble expression enzyme in E. coli, resulting in a 107 mg/L (2S)-eriodictyol titer. 15 Despite the efforts made, the high activity of F3′H/CPR in prokaryotes still faces challenges.…”
Section: Introductionmentioning
confidence: 99%